A simple procedure for synthesis of 3H-quinazolin-4-one hydrazones under mild conditions - Mohamed F. Abdel-Megeed; Mohamed M. Azaam; Gamal A. El-Hiti (Journal of Saudi Chemical Society, 2014)
Condensation of 6-bromo- and 6,8-dibromo-2-hydrazino-3-phenyl-3H-quinazolin-4-ones with d-sugars in the presence of a catalytic quantity of glacial acetic acid gave the corresponding hydrazones in good yields. Acetylation of hydrazones with acetic anhydride in anhydrous pyridine gave the corresponding acetyl hydrazones in high yields. Also, other hydrazones were synthesized from condensation of 2-hydrazino-3H-quinazolin-4-ones with aromatic aldehydes in the presence of a catalytic quantity of piperidine.